2017
DOI: 10.2105/ajph.2017.303711
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Social Services: A Study of Prenatal Case Management in Illinois

Abstract: Our analysis exhibits the potential for machine learning to move government agencies toward a more data-informed approach to evaluating risk and providing social services. Overall, such efforts will improve the efficiency of allocating resource-intensive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
0
21
0
6
Order By: Relevance
“…Modelos preditivos baseados em algoritmos de machine learning têm sido aplicados na área da saúde com potencial para auxiliar profissionais de saúde na tomada de melhores decisões, como mostram estudos recentes 12,31 . Entretanto, seu sucesso depende da disponibilidade de dados para a etapa de aprendizado de modelos preditivos e de capital humano para entender e desenvolver esses modelos de forma rigorosa e transparente.…”
Section: Discussão E Conclusõesunclassified
“…Modelos preditivos baseados em algoritmos de machine learning têm sido aplicados na área da saúde com potencial para auxiliar profissionais de saúde na tomada de melhores decisões, como mostram estudos recentes 12,31 . Entretanto, seu sucesso depende da disponibilidade de dados para a etapa de aprendizado de modelos preditivos e de capital humano para entender e desenvolver esses modelos de forma rigorosa e transparente.…”
Section: Discussão E Conclusõesunclassified
“…O estudo realizado por Correa et al 7 Outro estudo, realizado por Pan et al 24 , comparou a performance de algoritmos de aprendizagem supervisionada, como Naïve Bayes e random forest, para predição de partos considerados de risco, com base em dados históricos e em fatores de risco das mães, como estresse, condições socioeconômicas, má nutrição e idade, conseguindo uma performance preditiva 36% maior em comparação com análises estatísticas tradicionais.…”
Section: Aprendizagem Supervisionadaunclassified
“…Pan et al 24 Oliveira et al 25 Não supervisionada SOM Identificação de padrões de qualidade do ar em séries históricas.…”
Section: Random Forestsunclassified
“…Characteristic words of each SHRPW category and their Jaccard coe cients ANC, antenatal care; IPV, intimate partner violenceDiscussionResearch ndings to date have shown that preventive measures against child abuse could be taken by identifying the pregnant women at risk for abuse after childbirth 2,3,10,11. The Hawaii Healthy Start Program 10 uses a 15-item screening checklist during pregnancy for the early prevention of child abuse; if there is a possibility of a certain degree of risk, then trained paraprofessionals conduct home visits 11.…”
mentioning
confidence: 99%